Dental Treatment of Snoring and Sleep Apnea - Susanne Schwarting (Journal of Dental Problems and Solutions - Peertechz Publications, 2018)
Quite often it is a source of amusement and quite often it is hushed up: SNORING! One third of the adult population snores and knows the problems in everyday life which result from snoring. However, what a lot of people do not know is that snoring can be one indication of a serious health problem called obstructive sleep apnea (OSA). This is the reason why more than 90% of the people with sleep apnea go undiagnosed.